1981
DOI: 10.2337/diab.30.10.804
|View full text |Cite
|
Sign up to set email alerts
|

Organ Culture of Fetal Mouse Pancreas: The Effect of Culture Conditions on Insulin and Glucagon Secretion

Abstract: Seventeen-day-old mouse pancreas was grown in organ culture under various culture conditions and the insulin released into the medium, either chronically or during acute incubations, was measured. Three media, DME, RPMI 1640, and TC199, were tested, each at glucose concentrations of 1, 2, 3, and 4 g/L. Fetal pancreata maintained in RPM11640 at 4 g/L glucose secreted the most insulin over a 25-day period. Tissue grown in RPMI 1640 and DME secreted more insulin in higher glucose concentrations, but explants grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…Four age, sex and strain matched mice served as controls. Three weeks after STZ injection the diabetic animals were grafted with one half of one 17-day gestation foetal pancreas which had been in organ culture for 14 days (Collier et al, 1981). The grafts were placed either under the left renal capsule (systemic drainage) or on to the hilar surface of the spleen (portal drainage) (Mandel, Hoffman and Carter, 1981).…”
Section: Methodsmentioning
confidence: 99%
“…Four age, sex and strain matched mice served as controls. Three weeks after STZ injection the diabetic animals were grafted with one half of one 17-day gestation foetal pancreas which had been in organ culture for 14 days (Collier et al, 1981). The grafts were placed either under the left renal capsule (systemic drainage) or on to the hilar surface of the spleen (portal drainage) (Mandel, Hoffman and Carter, 1981).…”
Section: Methodsmentioning
confidence: 99%
“…Cultures of fetal islets have at least one advantage over these in vivo experiments. They make it possible to study separately the putative factors that may be involved in the maturation of B-cells (9)(10)(11)(12)(13)(14). A high concentration of glucose was found to be a necessary but insufficient factor to achieve full secretory maturation of fetal Bcells in some (13,14), but not all, studies (15).…”
mentioning
confidence: 96%
“…In previous studies we showed that foetal islets grown in high concentrations of glucose secreted more insulin into the medium than islets grown in physiological concentrations, but they responded poorly to an acute hyperglycaemic stimulus (Collier et al, 1981). In a separate preliminary study (Mandel et al, 1980) we suggested that islets grown in "hyperglycaemic' media functioned poorly as grafts in diabetic hosts when compared with islets cultured Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Pancreases were dissected from 17-day CKA/H/WEHI foetuses and each was explanted on to a piece of millipore filter (0 45 jum, Millipore Corporation, Bedford, Massachusetts) which was placed in a tube containing 1ml of medium supplemented with 15% foetal calf serum (FCS) so that the explants were at tlie cas-medium inlerface, as previously described (Collier et al, 1981). There were 4 culture groups: Dulbecco's modified Eagles (DME) medium with I g/1 glucose; DME with 4 g/1 glucose: RPMI 1640 wilh 1 g/1 glucose and RPMI 1640 with 4 g/1 glucose, with 9 replicates in each group.…”
Section: Tissue Culturementioning
confidence: 99%